Synchronous improvement of loss factors and storage modulus of structural damping composite with functionalized polyamide nonwoven fabrics. (15th March 2016) - Ni, Nannan; Wen, Yuefang; He, Delong; Yi, Xiaosu; Zhao, Zhongjie; Xu, Yahong
Abstract: Conventional structural materials and damping materials both don't combine excellent mechanical and damping properties at the same time, which makes them unable to meet the practical demand. Study on structural damping composites that possess higher mechanical and damping properties is becoming a hot research direction. Meanwhile dynamic mechanical analysis (DMA) could provide information on the mechanical and damping properties via storage modulus and loss factor, respectively, which makes it one of the most convenient and effective research methods on structural damping composites. In this paper, composites with polyamide non-woven fabrics (PNF) and functionalized PNF with crystalline thermoplastic polymer polyvinylidene fluoride (PVDF) and nanoscale carbon material vapor grown carbon fiber (VGCF) as interleaf materials are prepared firstly, then dynamic mechanical behaviors are measured and the microstructure is analyzed to study the effect of different interlayers on the mechanical and damping properties of the co-cured composites. The results indicate that PNF could improve the loss factors without significantly reducing the storage modulus, moreover, functionalized PNF with PVDF and VGCF are capable of further improving storage modulus and loss factors synchronously. Graphical abstract: Highlights: Adding Polyamide Nonwoven Fabrics (PNF) overcame the sharp decrease of mechanical property and heat resistance of conventional co-cured composite. Loss factors of the co-cured composites were reduced by adding layers of Polyamide Nonwoven Fabrics (PNF). Co-cured composite with PNF/PVDF exhibited better mechanical and damping properties synchronously. VGCF contributed to strengthening the mechanical property and heat resistance of the whole composite.